Insights into the influence of the molecular structures of fluorinated ionic liquids on their thermophysical properties. A soft-SAFT based approach - Ferreira, Margarida L. (2019)
FCT/MCTES - SFRH/BD/130965/2017 Investigador FCT 2014 (IF/00190/2014 to A. B. Pereiro and IF/00210/2014 to J. M. M. Araujo) projects PTDC/QEQ-EPR/5841/2014, PTDC/QEQ-FTT/3289/2014, and IF/00210/2014/CP1244/CT0003. This work was supported by the Associate Laboratory for Green Chemistry - LAQV, which is financed by national funds from FCT/MCTES (UID/QUI/50006/2019). Additional support was provided by the Center for Catalysis and Separation (CeCas Center) at Khalifa University, Abu Dhabi, through a research stay contract to M. L. Ferreira.